Nature Capital. An ecological transition and open space transformation phenomena - Renzo Lecardane (Agathón)
As indicated by the UN 2030 Agenda and the new European goals for 2030, Ecological Transition is at the basis of the new development model to reduce polluting emissions, prevent and combat land disruption, minimise the impact of productive activities on the environment and improve the quality of life and environmental security for future generations: on the one hand, orienting an ecological transition towards equity and collective well-being means rethinking the system of relations between man and the natural and built environment and, on the other hand, referring to the construction of social and cultural communities starting from environmental issues and land resources. In light of the above, this paper intends to reflect on the not-always-linear working method of the appropriation and transformation of open space concerning the definition of ‘fourth nature’ and ‘urban nature’ through three emblematic case studies. The aim is to go beyond the strictly anthropocentric view by focusing on the role of nature in the city through a selection, albeit not exhaustive, of innovative approaches to sustainable cities, the fight against climate change and the restoration of ecosystems, in a perspective of multi-species integration and the creation of regenerative ecosystems in the urban environment.